Successful cryopreservation of coral larvae using vitrification and laser warming. Issue 1 (December 2018) - Daly, Jonathan; Zuchowicz, Nikolas; Nuñez Lendo, C.; Khosla, Kanav; Lager, Claire; Henley, E.; Bischof, John; Kleinhans, F.; Lin, Chiahsin; Peters, Esther; Hagedorn, Mary
Abstract Climate change has increased the incidence of coral bleaching events, resulting in the loss of ecosystem function and biodiversity on reefs around the world. As reef degradation accelerates, the need for innovative restoration tools has become acute. Despite past successes with ultra-low temperature storage of coral sperm to conserve genetic diversity, cryopreservation of larvae has remained elusive due to their large volume, membrane complexity, and sensitivity to chilling injury. Here we show for the first time that coral larvae can survive cryopreservation and resume swimming after warming. Vitrification in a 3.5 M cryoprotectant solution (10% v/v propylene glycol, 5% v/v dimethyl sulfoxide, and 1 M trehalose in phosphate buffered saline) followed by warming at a rate of approximately 4, 500, 000 °C/min with an infrared laser resulted in up to 43% survival ofFungia scutaria larvae on day 2 post-fertilization. Surviving larvae swam and continued to develop for at least 12 hours after laser-warming. This technology will enable biobanking of coral larvae to secure biodiversity, and, if managed in a high-throughput manner where millions of larvae in a species are frozen at one time, could become an invaluable research and conservation tool to help restore and diversify wild reef habitats.